Reduced Order Models for Optimal Flow Control. (10th March 2021) - Strazzullo, Maria; Ballarin, Francesco; Rozza, Gianluigi
Abstract: Data assimilation models allow to fill the gap between numerical simulations and experimental data. Optimal control problems governed by parametrized partial differential equations PDE(µ) is suited for this kind of application, where you want to track problem solutions towards known quantities, given by data collections or previous knowledge. Still, the computational effort increases when one has to deal with nonlinear time‐dependent governing equations. Reduced order methods are an effective approach to solve data assimilation problems in a reliable and faster way. We apply the POD‐Galerkin methodology in environmental marine sciences where different parameters describe several physical configurations. We present a nonlinear time‐dependent tracking problem for velocity‐height solutions of shallow water equations.